Relationships between self-perceived and clinical expression of pain and function differ based on the underlying pathology of the human hip. - Nunley, Brandon.; Mulligan, Edward P; Chhabra, Avneesh.; Fey, Nicholas P; Wells, Joel. (Tufts University. Tisch Library., 2023)
Keywords: Femoroacetabular impingement syndrome, Developmental dysplasia of the hip, Patient-reported measures, Correlation analysis, Hip pain, Physical activity.; Springer Open.